Effectiveness of Mango Mistletoe on Lung Superoxide Dismutase in Hypertensive Rats Exposed to DOCA-Salt - Darma, Surya; Angie, Evelyn; Lubis, Yuliani Mardiati; Muharraran, Firdha (Poltekkes Kemenkes Palu, 2024)
Vascular disease, caused by oxidative stress and endothelial cell inflammation during hypertension's development, produces substantial mortality and morbidity. Mango mistletoe was tested for its effect on pulmonary superoxide dismutase (SOD) in hypertensive rats exposed to DOCA-salt in a preventative model. This study involves experimental quantitative research. SPSS was used for one-way ANOVA and post-hoc LSD testing. The population used was male Wistar rats (Rattus norvegicus). The samples used were 25 male Wistar rats divided into five treatment groups because of the Shapiro-Wilk test for normality analysis. The treatment group included a negative control group, a positive control group, and a group given different doses of mango mistletoe methanol extract: P1 at 75 mg/kgBW, P2 and P3 at 150 mg/kgBW, and P3 at 250 mg/kgBW. The study indicated that 250 mg/kg BW mango mistletoe extract increased SOD levels in DOCA-Garam-exposed Wistar white rats (Rattus norvegicus). Enhanced superoxide dismutase, malondialdehyde (MDA), ureum, creatinine, and renal histology see this. The normality of study data in the complete group assessing SOD, MDA, ureum, and creatinine levels showed a significance value larger than 0.05. The significance probability and one-way ANOVA test values are more than 0.05. The study found that mango mistletoe extract contains saponins, tannins, flavonoids, and triterpenoids that increase SOD levels and repair kidney cells damaged by hypertension in Wistar white rats. The study examined how mango mistletoe extract affects mouse hypertension. However, its conclusions should not be applied to humans. Clinical trials are needed to determine mango mistletoe extract's safety and efficacy for humans.